Ecology of Lepidoptera associated with bird nests in mid‐Wales, UK - Boyes, D; Lewis, O (Wiley, 2018)
1. Bird nests are ubiquitous but patchy resources in many terrestrial habitats. Nests can support diverse communities of commensal invertebrates, especially moths (Lepidoptera). However, there is a shortage of information on the moths associated with bird nests, and the factors influencing their abundance, diversity and composition. 2. Two hundred and twenty‐four nests, from 16 bird species, were sampled from sites in mid‐Wales (UK) and the moths that emerged from them were recorded. 3. Seventy eight percent of nests produced moths, with 4657 individuals of ten species recorded. Moth communities were dominated by generalist species rather than bird nest specialists. 4. Open nests built in undergrowth supported significantly fewer moths than nests in enclosed spaces (for example, nesting boxes). The occurrence of fleas was positively associated with the incidence and abundance of moths. There was no evidence that different nest types supported different moth communities.